Eksploration of Medicinal Plants as Utilizes in the Community Lamcot Village Darul Imarah District Aceh Besar: EKSPLORASI JENIS DAN PEMANFAATAN TUMBUHAN OBAT PADA MASYARAKAT DESA LAMCOT KECAMATAN DARUL IMARAH ACEH BESAR - Resmila Dewi; Rina Kurniaty; Cut Suraiya Wahyuni Utami; Erda Marniza; Widya Angreni (PT. ROCE WISDOM ACEH, 2024)
The use of plants as an alternative to traditional medicine has often been used by the people of Lamcot Village. However, until now there has been no clear identification of these types of plants scientifically. This study aims to determine the number and types of medicinal plants used by the people of Lamcot Village, their efficacy, and the plant organs used. This research was carried out from January to June 2024, located in a residential area of Lamcot Village, Darul Imarah District, Aceh Besar. This research uses survey and interview methods. The identification of medicinal plant types is carried out by matching the existing morphological characteristics with the images referring to the plant identification book. The results of the study showed that there were 25 collections of plants that were efficacious as traditional medicines used by the people of Lamcot Village. Plant organs used as medicine include roots, stems, leaves, flowers and rhizomes.